Two new species of Catonidia Uhler (Hemiptera: Fulgoromorpha: Achilidae) from southwestern China, with the first description of the male of Catonidia wuyishanana Wang & Huang - Chen, Xiang-Sheng; He, Ting-Ting (Zootaxa, 2009)
The following two species of the genus Catonidia Uhler, 1896 (Hemiptera: Fulgoromorpha: Achilidae: Achilini) from China are described as new to science: C. lii sp. nov. (southwestern China: Guizhou) and C. daozhenensis sp. nov. (southwestern China: Guizhou). The male of C. wuyishanana Wang & Huang, 1990 (southern China: Fujian) is reported and described for the first time. The generic characteristics are redefined. A key to the species of the world is presented.